Recombination and identification of human alpha B-crystallin - Wang, Rui (Int J Ophthalmol, 2018)
AIM: To recombine the human alpha B-crystallin (αB-crystallin) using gene cloning technology and prokaryotic expression vector and confirm the biological activity of recombinant human αB-crystallin. METHODS: Cloning the human αB-crystallin cDNA according to the nucleotide sequence of the human αB-crystallin, constructing the pET-28/CRYAB prokaryotic expression plasmid by restriction enzyme digestion method, and stably expressing transformed into the Escherichia coli (E. coli) DH5 alpha. The recombinant human αB-crystallin was purified by Q sepharose. By enzyme digestion analysis, Western blotting and sequencing, the recombinant human αB-crystallin was identified and the activity of its molecular protein was detected. RESULTS: Compared with the gene bank (GeneBank), the cloned human sequence of human αB-crystallin cDNA has the same open reading frame. Identification and sequencing of the cloned human αB-crystallin cDNA in prokaryotic expression vector confirmed the full length sequence, and the vector was constructed successfully. The E. coli containing plasmid pET-28/CRYAB induced by isopropyl-β-D-thiogalactoside successfully expressed the human αB-crystallin. Insulin confirmed that the recombinant human αB-crystallin has a molecular chaperone activity. CONCLUSION: The prokaryotic expression vector pET-28/CRYAB of recombinant human αB-crystallin is successfully constructed, and the recombinant human αB-crystallin with molecular chaperone activity is obtained, which lay a foundation for the research and application of the recombinant human αB-crystallin and its chaperone activity.